2016
DOI: 10.1128/mcb.00158-16
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia-Associated Nup214 Fusion Proteins Disturb the XPO1-Mediated Nuclear-Cytoplasmic Transport Pathway and Thereby the NF-κB Signaling Pathway

Abstract: c Nuclear-cytoplasmic transport through nuclear pore complexes is mediated by nuclear transport receptors. Previous reports have suggested that aberrant nuclear-cytoplasmic transport due to mutations or overexpression of nuclear pore complexes and nuclear transport receptors is closely linked to diseases. Nup214, a component of nuclear pore complexes, has been found as chimeric fusion proteins in leukemia. Among various Nup214 fusion proteins, SET-Nup214 and DEKNup214 have been shown to be engaged in tumorigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 81 publications
1
42
0
1
Order By: Relevance
“…Examples of genetic alterations targeting the nuclear transport machinery include chromosome rearrangements involving nucleoporin genes (e.g., NUP98 and NUP214) in hematologic malignancies [71] . The abnormal fusion proteins resulting from these translocations have been reported to disrupt XPO1mediated export [72,73] . Examples of nuclear transport factors abnormally expressed in tumors include the nuclear import receptors Importin β (see Dickmanns et al [64] and references therein) and Importina1 (see Christiansen and Dyrskjøt [74] , and references therein).…”
Section: Altered Nucleocytoplasmic Localization Of Proteins In Cancermentioning
confidence: 99%
“…Examples of genetic alterations targeting the nuclear transport machinery include chromosome rearrangements involving nucleoporin genes (e.g., NUP98 and NUP214) in hematologic malignancies [71] . The abnormal fusion proteins resulting from these translocations have been reported to disrupt XPO1mediated export [72,73] . Examples of nuclear transport factors abnormally expressed in tumors include the nuclear import receptors Importin β (see Dickmanns et al [64] and references therein) and Importina1 (see Christiansen and Dyrskjøt [74] , and references therein).…”
Section: Altered Nucleocytoplasmic Localization Of Proteins In Cancermentioning
confidence: 99%
“…Additionally, we observed that the fusion proteins sequestered endogenous NPC components: NUP88 ( Figure 2D) and NUP62 ( Figure 2E NUP214 fusion proteins are sensitive to nuclear export inhibition CRM1 inhibition by LMB leads to the dissolution of nuclear bodies containing NUP214 fusion proteins, in LOUCY and in transfected cells 17,18 . We confirmed these previous results for SET-NUP214 in LOUCY cells here (Figure 3 A-…”
Section: Nup214 Fusions Accumulate the Nuclear Export Factor Crm1 In mentioning
confidence: 89%
“…The C-terminal phenylalanine-glycine (FG) repeat domain of NUP214 exhibits multiple CRM1-binding sites, which are preserved in SET-NUP214 and DEK-NUP214 [16][17][18][19] . In fact, both fusion proteins can bind CRM1 and its co-factor, the small GTPase Ran, and inhibit the nuclear export of NES-containing proteins and RNPs 17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they are less well characterized than the Nup98 fusions described later, some mechanisms have been demonstrated for Nup214 fusion proteins. Recently, the Set and Dek fusions to Nup214 have been shown to alter gene expression regulation by inhibiting nuclear export of mRNA and transcription factors by tethering the export factors Crm1 and Nxf1 to nucleoplasmic aggregates [126]. In various cancers another cytoplasmic filament nucleoporin, Nup358, is fused to Alk, Abl, and Fgfr.…”
Section: Npcs In the Development And Progression Of Cancersmentioning
confidence: 99%